Examining the Relationship Between Lecturer Service Quality and Student Retention - Elizabeth Meiske Maythy Lasut (Al-Qalam Institue, 2026)
This study aims to examine the relationship between lecturers’ service quality dimensions—assurance, tangibles, empathy, reliability, and responsiveness—and student retention in higher education. A quantitative correlational design was employed involving 212 first-year, second-semester students selected through convenience sampling. Data were collected using a self-constructed questionnaire based on a 5-point Likert scale and analyzed through descriptive statistics and Pearson Product-Moment correlation. The findings revealed that all dimensions of lecturers’ service quality were rated at a high level, with tangibles obtaining the highest mean score (4.05) and reliability the lowest (3.85). Student retention was also categorized as high (mean = 3.65). Furthermore, all service quality dimensions showed positive and significant relationships with student retention. Assurance (r = 0.453) and tangibles (r = 0.450) demonstrated the strongest relationships, followed by empathy (r = 0.337), reliability (r = 0.331), and responsiveness (r = 0.169). The study implies that higher education institutions should prioritize strengthening lecturers’ competence and professionalism while improving reliability in teaching practices to enhance student retention.